كسرة همزة "إن" فى القرآن الكريم سورة البقرة والقصص - Ari Khairurrijal Fahmi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2018)
The objective of this research is to acquire a deep understanding of the "Kasrah Hamzah Inna" on Alquran Alkareem Albaqarah and Alqashas Epistles, which consist of 149 verses. The research method used in this study is a descriptive qualitative method using content analysis of the verses of Quran. The result showed that there are 97 % the "Kasrah" was compulsory, and 3% was uncompulsory. The most verses appear with "Inna" is at the beginning of the kalimah and after the verb "Qaul" . The 97% of kasratu Inna is compulsory, it's divided into five: 1. At the beginning of the sentence amounted to 80 (54%) (and it is divided into 5; a.hakikat it was 13 (16%), b, hokum it was 3 (4%), c.ibtidaiyah it was 12 (15%), d. isti'nafiyyah it was 12 (15%), e. ta'liliyyah 40 (50%)). 2. After the Conjunction it was 1 (1%). 3. After the answer of oath sentence, it was 1 (1%). 4. After the words amounted to 31 (21%). After the sentence torch circumstances, it was 5 (4%). Meanwhile, the position of noncompulsory kasratu Hamzah Inna was founded after faa aljazaa, only 5 times (3%). The results show that many types of kasrah hamzah Inna were founded in albaqarah and alqashas.